2007
DOI: 10.1007/s00464-007-9490-7
|View full text |Cite
|
Sign up to set email alerts
|

Who will fail laparoscopic Nissen fundoplication? Preoperative prediction of long-term outcomes

Abstract: In a cohort with 11 years follow-up after LNF, factors predictive of a successful outcome include preoperative response to ARM, typical symptoms, and BMI < 35 kg/m2. Patients with atypical symptoms, no response to ARM, or morbid obesity should be informed of their higher risk of failure. Some patients in these groups do have successful outcomes, and further research may clarify which of these patients can benefit from LNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(149 citation statements)
references
References 32 publications
(46 reference statements)
4
135
3
3
Order By: Relevance
“…To date, few studies have examined the long-term efficacy and durability of traditional anti-reflux procedures such as Nissen fundoplication in the setting of severe obesity, and results have been conflicting [18][19][20][21][22] . It has been suggested that laparoscopic anti-reflux surgery is associated with a higher failure rate in obese patients because of intraoperative technical difficulties as well as increased intra-abdominal pressure postoperatively [28] . Nevertheless, others have reported equivalent outcomes in obese and normal weight individuals [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies have examined the long-term efficacy and durability of traditional anti-reflux procedures such as Nissen fundoplication in the setting of severe obesity, and results have been conflicting [18][19][20][21][22] . It has been suggested that laparoscopic anti-reflux surgery is associated with a higher failure rate in obese patients because of intraoperative technical difficulties as well as increased intra-abdominal pressure postoperatively [28] . Nevertheless, others have reported equivalent outcomes in obese and normal weight individuals [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The management of GORD in obese patients remains contentious with no consensus or published guidelines. Data are conflicting regarding the long-term efficacy of fundoplication in obese individuals compared with normal weight counterparts [18][19][20][21][22] . Nevertheless, most surgeons would agree that treatment of GORD in obese and non-obese patients requires different strategies [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Although not unanimously, some series show poorer outcomes for obese patients [18,22] that undergo a fundoplication likely due to a more demanding operation with longer operative times [23] and more complications.…”
Section: Patient Selectionmentioning
confidence: 99%
“…[ [16][17][18][19] With the exception of obesity, these predictors cannot be changed in the majority of patients.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation